Мінливість кількісних ознак селекційно-цінних зразків перцю солодкого за умов апоміктичного розмноження - Гарт, О.Ю.; Кондратенко, С.І.; Куракса, Н.П. (Фактори експериментальної еволюції організмів, 2014)
Aims. A comparative analysis of the effectiveness of stabilization genetic breeding and quantitative traits of samples of sweet pepper under free pollination and apomictic reproduction. Methods. In the experiment used a line of sweet pepper, which were derived from breeding and of forms that can generate apomictic seed after developed a method of stimulating the growth of unfertilized seed embryos. Results. A comparative analysis of the variability of quantitative traits 8 (“Height of plant”, “Leaf length”, “Width leaf”, “Turning fruit”, “Fruit length”, “Wall thickness fruit”, “Number of fruits per plant”, “Weight of the fetus”) selection and designs of sweet pepper by different methods of reproduction – by free pollination of plants and by means of induced apomixis. Found that the most genetically stable for phenotypic expression were quantitative traits of plants belonging to populations of apomictic lines. Conclusions. Thus, in our studies at the level of biometric analysis of sweet pepper plants have been proven advantages of the developed method induced apomixis, which allows for more efficient conduct genetic stabilization source of breeding material in contrast to the traditional method, which is based on long-time family selection of hybrid populations of plants.

Key words: sweet pepper, induced apomixis, reproduction, quantitative trait, line.